Evaluasi pemungutan pajak restoran berdasarkan Peraturan Daerah Kota Ternate Nomor 15 Tahun 2014 tentang pajak restoran di Badan Pengelolaan Pajak dan Retribusi Daerah Kota Ternate - Abd Madjid, Zaena; Sabijono, Harijanto; Mintalangi, Syermi S.E. (Riset Akuntansi dan Portofolio Investasi, 2024)
Restaurant tax is a source of regional revenue that contributes significantly to the increase of Regional Original Domestic Product (PAD) due to the large number of culinary tourisms in Ternate City. This research aims to evaluate the implementation of restaurant tax collection based on Ternate City Regional Regulation Number 15 of 2014 concerning Restaurant Tax at the Ternate City Regional Tax and Levy Management Agency. This type of research is descriptive qualitative. The research results show that the collection carried out at BP2RD Ternate City is in accordance with Ternate City Regional Regulation Number 15 of 2014 regarding restaurant tax. However, there are also areas that do not comply with the regional regulations, namely designated areas. This shows that BP2RD Ternate City has not fully implemented the collection in accordance with the applicable regulations, but has only partially implemented the collection in accordance with the applicable regulations.